Evaluation of the indicators of the dehydration induced by furosemide and the hydro electrolytic balance changes in horses (Research, Society and Development, 2020)
Objective: The aim of this study was evaluation of clinical and hematological and hemogasometric parameters resulting from experimentally induced furosemide dehydration in horses. Methods: Six adult male horses were submitted to the protocol of induction of dehydration with furosemide and kept in water and feeding fasting for 72 hours. Clinical, hematological and hemogasometric examinations were performed every 12 hours. Clinical parameters were correlated with body weight loss to identify those who best represent the clinical picture of dehydration. Results: Mean weight loss was 13.5% after 72 hours. The capillary refill time showed the best correlation index (r) of 0.95, (p-value = 0.001), followed by BUN , r = 0.94, heart rate, with negative correlation with weight loss, r = -0.91 (p-value = 0.005), packed cell volume, r = 0.78 (p-value = 0.038 Plasma protein has further increased to 8.4 ± 0.5 g / dL and urea increased by over 100% at the end of the study. Was also observed an increase in sodium concentration and progressive decrease in chloride and potassium concentrations during the evaluated period. The pH rose from 12 hours and remained high until complete the 72 hours. There was also an increase in plasma bicarbonate concentration from 24 hours, exceeding the reference limits. Conclusions: Given these results, it can be concluded that the dehydration protocol induced a light hypertonic dehydration, confirmed by the slight increase in plasma osmolarity, hyperproteinemia, hypochloremia with metabolic alkalosis, confirmed by the average values of strong ions difference during throughout the dehydration process.